Improvement of mechanical properties of graphene/substrate interface via regulation of initial strain through cyclic loading. (November 2018) - Du, Hongzhi; Xue, Tao; Xu, Chaochen; Kang, Yilan; Dou, Wenbo
Highlights: The redundant strain of graphene on top of flexible substrate was proposed and characterized; Graphene/PET interfacial mechanical properties could be effectively improved by appropriate cyclic loading treatment; The micro-mechanism of the cyclic loading for the optimization of the mechanical properties of the tangential interface was analyzed. Abstract: To analyze the effect of initial strain of graphene, a systematic experimental investigation of the mechanical properties of graphene/polyethylene terephthalate (PET) interface was performed. Several graphene/PET specimens were designed by applying various cyclic loading treatments. The Raman mapping method was used to compare the strain field information before and after these cyclic-loading treatments. The analysis suggests that the initial strain of graphene can be effectively reduced by repeated interfacial shear deformation and load transfer, which improves the resulting interfacial bonding degree. After the cyclic loading treatments, the graphene samples were stretched using a micro-tensile device, and the strain distributions of graphene were measured using Raman spectroscopy. The debonding evolution was monitored, and the interfacial parameters of graphene for the different treatments were quantitatively compared. The experimental results indicated that the graphene/PET interfacial properties can be effectively improved using cyclic loading treatment. Finally, the internal mechanism for improvement of the tangential interfacial properties was analyzed from micro-nano and atomic viewpoints. This work provides a reference for engineering application of graphene interface improved via strain regulation.